The Shifting Landscape of Elderly Care: Implications of Youth Migration in Nigeria - Egbochuku, Obiageli Ogochukwu; Atedhor, Chinwe Nneamaka (NIU Journal of Social Sciences, 2025)
Youth migration, a widespread phenomenon, has significant implications for the health and wellbeing of the elderly left behind. This review paper synthesizes existing literature to examine the complex relationships between youth migration and the health of older adults. The paper explores how youth migration affects the physical, emotional and social health of the elderly. It also examines institutional and policy frameworks in Nigeria to address the health and wellbeing of the elderly.  Literature was sourced from relevant databases such as PubMed, Science Direct and goggle scholar using key words such as Youth migration, elderly health, Nigeria and caregiving. Inclusion criteria for literature was based on scholarly articles in reputable journals within 15years frame (2010-2025) including data/reports from national and international organizations/agencies. It also considered articles that examined youth migration in sub-Saharan Africa especially the Nigerian context with a focus on international migration.  Findings from this study provide valuable information on the complex interactions between youth migration, caregiving deficits, social isolation and elderly health. This paper has established that there is high rate of youth migration with massive brain drain especially in the health sector. Specifically, among others, findings indicate that youth migration significantly impacts health of the elderly especially their mental health, although some may enjoy remittances. It however, emphasized that caregiver deficit led to social and economic consequences that exacerbate challenges in the health of the elderly. Consequently, the findings underscore the need for policy and community-based interventions supporting elderly individuals with migrant children. It also advocates that healthcare access and utilization should target elderly individuals both rural and urban settings. Furthermore, there is the need for Nigerian government to provide enabling environment hence discouraging migration of its citizens. Keywords: Youth migration, Elderly health, Nigeria, Caregiving